THE IMPLEMENTATION OF BILLBOARD ARRANGEMENT POLICY AT SEMARANG CITY - Gutami, Gabrela Dhina; Lituhayu, Dyah (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2020)
ABSTRACT The rapid growth of population in Semarang City is the main target of entrepreneurs to promote goods and services by using billboard as a promotional media. The problem of organizing billboards in Semarang City is the number of billboards installed illegally, thus damaging the visual quality of the city. One of the efforts is the implementation of supervision in billboard arrangement conduct by the Departement of Spatial Planning (Distaru) Semarang City. The purpose of this research is to describe how the implementation of supervision carried out by the implementers based on the regulations, then to identifying the factors that affect the implementation of supervision policies in billboards arrangement. This research uses descriptive qualitative research method with data collecting technique through interview, observation, and documentation. The results showed that Dinas Spatial Planning Semarang City had tried to implement the policy, even supervision of the implementation of the billboards as an effort to arrangement the billboards had been carried out according to the procedure, but the criteria for the location of the billboard placement stipulating that the billboards could only be posted on private land were considered difficult for the billboard organizers. In this implementation of arrangement billboard policy, there are still many obstacles, such as: 1) Lack of human and financial resources; 2) Lack of public awareness; 3)Lack of coordinating between the implementing agencies with the target group; and 4) Lack of socialization. Suggestions that can be given are to increase the amount of human and financial resources, improve coordinating between implementing agencies and the target group, and reinforce sanctions against violators in organizing billboards.